(untitled) (Bangladesh Journal of Botany, 2021)
The soil nutrient characteristics under three vegetation types of arbor ( I ), shrub ( II ) and herb ( III ) were studied by mathematical statistics method combined with field investigation and indoor detection analysis. The change characteristics of soil nutrients under different land use patterns were discussed. The results showed that the average contents of soil organic matter, total nitrogen, available phosphorus and available potassium were 21.30 and 0.65 g/kg, 3.67 and 67.61 mg/kg, respectively. Compared with grassland, woodland has better effect on fertilizer conservation in the Loess Plateau. In the process of soil nutrient improvement, the nutrient indexes such as organic matter, total nitrogen, available phosphorus and available potassium increased synchronously, and the soil alkaline environment that was not conducive to plant growth was also gradually improved. In the correlation between soil nutrients, available phosphorus and available potassium have good relative independence. In the future, organic fertilizer should be applied in this area, and nitrogen and phosphorus fertilizers should be supplemented to improve soil organic matter, nitrogen and phosphorus content, and to ensure soil nutrient balance by optimizing fertilization methods. In addition, in the case of uneven distribution of soil nutrients in the soil profile, it is recommended to take appropriate soil ploughing and reasonable human management measures to improve soil nutrient status, achieve high-quality sustainable development of soil, and promote the positive succession of vegetation communities. Bangladesh J. Bot. 50(3): 969-976, 2021 (September) Special